Vnovična zmaga ekipe Pravne fakultete Univerze v Ljubljani na CEEMC - Vlahek, Ana (Pravnik, 2023)
For the second year in a row, the team from the University of Ljubljana Faculty of Law won the Central and Eastern Europe Moot Competition – CEEMC, which is organised by the British Law Centre under the auspices of the University of Cambridge and the Court of Justice of the EU. The members of the team were undergraduate students Lea Zahrastnik and Ana Mestinšek Mubi, and a postgraduate student Peter Grašič who worked tirelessly and diligently throughout the entire preparation period in an excellent and respectful team atmosphere. They were coached by former successful competitors of the faculty in moot court competitions, Žana Lapajne, Masha Korošec and Walter Maj Vidmar under the mentorship of Assoc. Prof., Assoc. Prof. Ana Vlahek. At the final part of the competition, which took place in Croatian Dubrovnik, in addition to the team victory, student Lea Zahrastnik received the highest speaker award – the Best Speaker Award.
Keywords: British Law Centre; CEEMC; moot court; ocene in poročila; Pravna fakulteta Univerze v Ljubljani; pravo; študenti; študentska tekmovanja; Univerza v Cambridgeu